Legume Crops Prospects, Production and Uses - Hasanuzzaman, Mirza (IntechOpen, 2020)
In a sustainable agricultural system, legume crops are one of the essential components. However, improving the productivity of legume crops and improving their tolerance to adverse environments are essential tasks for plant biologists. This book includes nine comprehensive chapters addressing various aspects of legume crop biology, production and importance. There are several chapters on the adaptation of legumes to an adverse environment. Particular focus is provided on the sustainable production of legume crops under changing environments. This book will be useful for undergraduate and graduate students, teachers, and researchers, particularly from the field of Crop Science, Soil Science, Plant Breeding and Agronomy.